Hardware Supported Frame Correction in Touch Screen Systems - For a Guaranteed Low Processing Latency - Nilsson, Gustav (My University, 2021)
Devices utilizing touch input have become prevalent in various areas. Touch inter faces are intuitive and easy to use as they attempt to mimic real-life actions such as grabbing and moving objects around. However, the illusion of manipulating real-life objects is broken due to high end-to-end latencies, where objects are visibly lagging behind the finger. A 1 ms latency is required for good touch interactions, optimally calling for 1000 frames per second (fps) content. This thesis investigates creating an acceleration system that adjusts finished rasterized graphics based on the latest touch-input, hiding the processing latency and producing high frame rates. First, a list of the required functionality for the acceleration system is defined. Next, a hardware architecture is designed, which is implemented in VHDL. Lastly, the architecture is tested on an FPGA card connected to a touch screen and a single board computer running two test applications. The resulting architecture achieves a guaranteed 83µs processing latency in 1024x768 at 120fps while supporting the most common single-touch user interfaces. Predictably, the system can support 1000fps in 4K if implemented as an ASIC with sufficient off-chip memory bandwidth. Despite 1000fps being the long-term goal, the system can potentially provide significant im provements to devices with displays updating at the standard 60-120Hz. Although promising, details on how to best implement the acceleration in a real-life system are yet to be investigated.
Keywords: touch input; latency; high frame rate; computer architecture; computer graphics